2022
DOI: 10.3390/ma15228089
|View full text |Cite
|
Sign up to set email alerts
|

Achievements and Perspectives on Fe-Based Shape Memory Alloys for Rehabilitation of Reinforced Concrete Bridges: An Overview

Abstract: Reinforced concrete (RC) bridges often face great demands of strengthening or repair during their service life. Fe-based shape memory alloys (Fe-SMAs) as a kind of low-cost smart materials have great potential to enhance civil engineering structures. The stable shape memory effect of Fe-SMAs is generated by, taking Fe-Mn-Si alloys as an example, the martensite transformation of fcc(γ) → hcp(ε) and its reverse transformation which produces considerable recovery stress (400~500 MPa) that can be used as prestress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…It also has coarse grains, easy fracture of grain boundaries, and poor phase transition stability, resulting in slow progress [ 55 ]. Fe-based alloy has attracted increasing attention because of its comparable stress and low cost compared with Ni-Ti alloy, but its poor corrosion resistance and unstable performance mean that it is not as widely used as Ni-Ti alloy [ 56 , 57 ]. Figure 6 shows the ultimate stress and recovery strain of commonly used building materials and different types of SMA.…”
Section: Sma Characteristics and Typesmentioning
confidence: 99%
“…It also has coarse grains, easy fracture of grain boundaries, and poor phase transition stability, resulting in slow progress [ 55 ]. Fe-based alloy has attracted increasing attention because of its comparable stress and low cost compared with Ni-Ti alloy, but its poor corrosion resistance and unstable performance mean that it is not as widely used as Ni-Ti alloy [ 56 , 57 ]. Figure 6 shows the ultimate stress and recovery strain of commonly used building materials and different types of SMA.…”
Section: Sma Characteristics and Typesmentioning
confidence: 99%
“…This unique property has propelled extensive research into various SMA materials for diverse applications across sectors including aerospace, automotive, and biomedical industries [ 1 , 2 , 3 ]. Amongst the array of SMAs, Fe-Mn-Si-based alloys have attracted considerable interest due to their cost-effectiveness, excellent mechanical properties, and particularly, their potential for significant ductility and high damping capacity [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research into these conventional processes has focused extensively on understanding the thermomechanical behaviors and the effects of alloying elements on the martensitic transformation, which is fundamental to the shape memory effect. Studies have shown that the addition of elements like Cr and Ni can significantly influence phase transformation temperatures, improving mechanical properties and corrosion resistance [ 8 , 10 ]. Especially, adding V and C elements can improve pseudo-elasticity via decreasing the grain size and precipitation of VCs [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Discovered in 1982 by Sato et al [6][7][8] in a seminal series of papers on Fe-Mn-Si single crystals, and later by Murakami et al [9] in polycrystals, the Fe-Mn-Si-based family evolved towards Fe-Mn-Si-Cr-Ni, to improve the corrosion resistance [10][11][12]. Because of the indicated properties, this family of SMA is becoming extremely suitable for numerous applications, particularly within the field of civil engineering [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. This material exhibits a martensitic transformation from an FCC γ austenite to an HCP ε martensite, which occurs by the motion of a/6<112> Shockley partial dislocations on every two (111) close-packed planes of the FCC structure, according to the model of Olson and Cohen [29].…”
Section: Introductionmentioning
confidence: 99%